CAPITAL MARKET INTEGRATION Evaluation and Measurement Sovereign Bond Market - Víťazka, Peter (2013)
The paper focuses on capital market integration at sovereign bond market in eleven selected euro zone countries (Austria, Belgium, Finland, France, Germany, Greece, Ireland, Italy, Netherlands, Portugal, and Spain). The first main objective is to test the degree of capital market integration before and after the crisis using Germany as a benchmark country and also among them as well. Secondly it evaluates and provides reasons of capital integration in time. The examination is applied through i) sigma convergence ii) yield spreads iii) correlation matrix iv) cointegration tests. I found almost zero yield differences before crisis. After 2008 results show segmentation in euro zone countries with certain special characteristic for countries with high credit ratings.